Efektivitas Aplikasi Pupuk Kascing dengan Berbagai Media Tanam terhadap Pertumbuhan dan Produksi Tanaman Okra (Abelmoschus esculentus L.) - Diana Ananta Syaputri; Najla Lubis; Maimunah Siregar (Politeknik Kampar, 2026)
Okra (Abelmoschus esculentus L.) is a horticultural commodity with high economic potential, but its production in Indonesia is still not optimal. One of the obstacles in okra cultivation is the use of inappropriate planting media and less than optimal fertilization. This study aims to determine the effectiveness of vermicompost application with various planting media on the growth and production of okra plants. This study used a Factorial Randomized Block Design (RAK) consisting of 2 factors with 16 treatment combinations and 3 replications. Factor I is the planting media: K0 = topsoil / control; K1 = topsoil + TKKS (1:1); K2 = topsoil + rice husk (1:1); K3 = topsoil + rice husk charcoal (1:1). Factor II is the dose of vermicompost fertilizer consisting of 4 levels, namely M0 = (control / no treatment); M1 = 100 g / polybag; M2 = 200 g / polybag; M3 = 300 g / polybag. Observed parameters included plant height, stem diameter, number of fruits per plot, number of fruits per sample, fruit weight per plot, and fruit weight per sample. The results of this study indicate that the best growing medium treatment was the combination of K1 = topsoil + TKKS (1:1), which affected several growth parameters and fruit number. The vermicompost fertilizer treatment at a dose of 300 g/polybag (M3) consistently provided the best results for most plant growth and yields.